Temporal and Spatial Resolution of Activated Plant Defense Responses in Leaves of Nicotiana benthamiana Infected with Dickeya dadantii - Pérez-Bueno, María L.; Granum, Espen; Pineda, Mónica; Flors, Víctor; Rodriguez-Palenzuela, Pablo; López-Solanilla, Emilia; Barón, Matilde (Frontiers in Plant Science, 2016)
The necrotrophic bacteria Dickeya dadantii is the causal agent of soft-rot disease in a broad range of hosts. The model plant Nicotiana benthamiana, commonly used as experimental host for a very broad range of plant pathogens, is susceptible to infection by D. dadantii. The inoculation with D. dadantii at high dose seems to overcome the plant defense capacity, inducing maceration and death of the tissue, although restricted to the infiltrated area. By contrast, the output of the defense response to low dose inoculation is inhibition of maceration and limitation in the growth, or even eradication, of bacteria. Responses of tissue invaded by bacteria (neighbouring the infiltrated areas after 2-3 days post-inoculation) included: i) inhibition of photosynthesis in terms of photosystem II efficiency; ii) activation of energy dissipation as non-photochemical quenching in photosystem II, which is related to the activation of plant defense mechanisms; and iii) accumulation of secondary metabolites in cell walls of the epidermis (lignins) and the apoplast of the mesophyll (phytoalexins). Infiltrated tissues showed an increase in the content of the main hormones regulating stress responses, including abscisic acid (ABA), jasmonic acid (JA) and salicylic acid (SA). We propose a mechanism involving the three hormones by which N. benthamiana could activate an efficient defense response against D. dadantii.